SIX SIGMA UNTUK ANALISIS KEPUASAN PELANGGAN TERHADAP PERSEPSI KUALITAS PROVIDER KARTU GSM PRABAYAR - Dina Rosmalia Listya Utami; Mustafid Mustafid; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
The company is currently competing industry in offering a good product in the form of goods or services in order to attract consumers. Competition industrial companies also occur in companies engaged in the telecommunications sector that influence the cellular telecommunications services company. In 2000 PT Indosat and PT Telkomsel was licensed as an operator National GSM 1800 as mandated by the Telecommunications Act No. 36/1999. In recent years, the Provider of Indosat and Telkomsel occupied the top two in terms of number of customers and the profit generated. This study aimed to analyze the level of customer satisfaction on the perception of the quality of the GSM prepaid card provider used by using six sigma method that becomes an approach to reduce the variability of the process through the use of statistical tools. In this study, the overall process is in a state that has not been well despite being in the category of satisfied but do not meet the targets used. DPMO results obtained from the Provider Indosat and Telkomsel to dimensions of technical quality and functional quality with a target of 8 each is 189718,8; 180625; 102343,8; 105250 with the sigma level 2,37; 2,41; 2,76 and 2,32. As for the dimensions of technical quality and functional quality with the target 9 on each Provider DPMO results obtained for 279750; 271666,7; 202083,3; 204666,7 with sigma level 2,08; 2,41; 2,33 and 2,32. These results are still far from the expected target is 3,4 DPMO and 6-sigma. Keywords: Six Sigma, DPMO, Service Quality, Customer Satisfaction.